04.02: Plastic behaviour of polygonal hollow sections in bending. (13th September 2017) - Rohr, Katharina; Knoedel, Peter; Ummenhofer, Thomas
ABSTRACT: Steel poles of polygonal sections are an economic alternative to circular hollow sections for use as lighting towers or transmission line pylons. Especially for transmission lines, the design of the poles is intended to become more compact to avoid land usage and to obtain an inconspicuous appearance. If the pole diameter is reduced, the slenderness of the sections needs to be reduced as well to achieve the desired resistance, but an increasing wall thickness disproportionately reduces the cost‐effectiveness of the structure. The European design rules for overhead electrical lines [1] do not allow using the plastic behaviour of stocky sections, which reduces the advantages of compact sections. In modern standards for steel structures, such as Eurocode 3 (EC3) [2], activating plastic reserves is generally acknowledged state of the art. According to EC3‐1‐1, the slenderness of the profile decides on the allocation to cross section class 1 or 2, where plastic design is allowed, class 3, where only elastic behaviour is used or class 4, where local buckling is assumed. When changing from class 2 to class 3 sections, this standard provides a sudden drop in resistance, which has long been recognised to be unjustified. Research has been done to overcome this mismatch for circular hollow sections [3]. In this paper the transition between the plastic bending moment capacity and the limit state of buckling is investigated to identify the ultimate load of polygonal sections. The investigated polygon of 16 edges can be treated as a collection of plate strips using the plate buckling design rules EC3‐1‐5 for cross sections class 4. Detailed examinations illustrate the inconsistency of EC3 in the bending capacity of compact sections right before the start of stability problems. On the basis of experimental data gained from full‐scale bending tests, along with imperfection measurements via laser scanning, numerical investigations have been performed. These results suggest that the bending moment capacity can be increased above the calculated elastic capacity with more compact sections, but might be overestimated when calculating the full plastic capacity according to EC3‐1‐1.